Psychological Analysis of Indoor Hockey Athletes when Competing Against Superior Teams - Octavian, Raihan Bima; Rusmana, Ruslan; Septiana, Rama Adha (Journal of Physical and Outdoor Education, 2024)
The purpose of this study was to determine the psychological quality of indoor hockey athletes when competing against superior teams. The population in this study were STKIP Pasundan indoor hockey athletes, who amounted to 25 people. The sampling technique used is total sampling, by taking the entire population as a sample. The instrument in this study used the sport competition axienty test (SCAT). The research method used is descriptive quantitative with a survey approach. Data collection techniques through Google Form distributed through the Whatsapp application and analyzed using the percentage formula with the requirements for calculating data analysis using the calculation of the average value. The results of the research analysis show that there are differences in the level of psychological quality among athletes. 1 athlete showed excellent quality (4%), 10 athletes showed good quality (40%), 9 athletes showed sufficient quality (36%), 2 athletes showed poor quality (8%), and 3 athletes showed very poor quality (12%). Thus, it can be concluded that the psychological quality of the STKIP Pasundan Cimahi indoor hockey team athletes is in a good category, although there is a need to improve the quality of 2 athletes with poor quality (8%) and 3 athletes with very poor quality (12%). This information can be a guideline for coaches and athletes to further develop the psychological aspects of athletes in order to achieve optimal performance.